2006
DOI: 10.1016/j.geothermics.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Flow channeling in a single fracture induced by shear displacement

Abstract: The effect on the transport properties of fractures of a relative shear displacement u of rough walls with complementary self-affine surfaces has been studied experimentally and numerically. The shear displacement u induces an anisotropy of the aperture field with a correlation length scaling as u and significantly larger in the direction perpendicular to u. This reflects the appearance of long range channels perpendicular to u resulting in a higher effective permeability for flow in the direction perpendicula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 19 publications
7
56
0
2
Order By: Relevance
“…It was found that fluid flows in rock fractures through connected and tortuous channels that bypass the contacts areas. However, the effects of contacts and the channel distribution patterns on the fluid flow and tracer transport processes in a rock fracture, and their change due to both normal stress and shear displacements, have not been fully understood, even though the effect of the mechanical processes on the fluid flow and transport phenomena has been investigated experimentally and numerically by considering normal stresses without shear [4][5][6] or shear displacement without (or very weak) normal stress [5,[7][8]. This is mainly due to the difficulties of quantitative measurements of changing fracture surface roughness and aperture during laboratory coupled stress-flow tests, especially the contact areas, as well as a number of technical difficulties in laboratory shear-flow testing, most notably the sealing of fluid during shear.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that fluid flows in rock fractures through connected and tortuous channels that bypass the contacts areas. However, the effects of contacts and the channel distribution patterns on the fluid flow and tracer transport processes in a rock fracture, and their change due to both normal stress and shear displacements, have not been fully understood, even though the effect of the mechanical processes on the fluid flow and transport phenomena has been investigated experimentally and numerically by considering normal stresses without shear [4][5][6] or shear displacement without (or very weak) normal stress [5,[7][8]. This is mainly due to the difficulties of quantitative measurements of changing fracture surface roughness and aperture during laboratory coupled stress-flow tests, especially the contact areas, as well as a number of technical difficulties in laboratory shear-flow testing, most notably the sealing of fluid during shear.…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi les écarts d'approximativement un ordre de grandeur obtenus en laboratoire par . Ces trois études révèlent un mécanisme similaire : la formation dans le plan de faille de canaux perpendiculaires au glissement favorisant significativement les écoulements dans la direction normale au jeu, soit KTN>Krr- Auradou et al (2006) montrent que cette chenalisation est générée lors du cisaillement par la rugosité paramétrée des parois de la fracture (décrites ici par une fonction auto-affine). Ce mécanisme est extensible à l'échelle des failles naturelles, les virgations décimétriques à décamétriques du plan de faille produisant par décompression une chenalisation des écoulements selon un schéma sensiblement analogue , illustré par la figure 1.4-a.…”
Section: Changements D'échelleunclassified
“…Il s'agit notamment de déterminer les mouvements réels et les vitesses de transfert d'un soluté en hydrogéologie des contaminants (e.g., Gierczak et al, 2005), d'anticiper les effets d'une exploitation à long terme d'un réservoir hydrique discontinu, de caractériser la formation et les comportements des gisements tectoniques pétroliers (Fisher et Knipe, 2001), ou encore de quantifier les surfaces d'échanges eau-roche dans le cadre de recherches sur l'extraction d'énergie géothermique (Dezayes et al, 2004;Auradou et al, 2006 .…”
Section: Introduction Generaleunclassified
“…Whereas, natural fractures usually display a strong hydraulic complexity coming from the aperture anisotropy induced by the roughness of two fracture walls (Isakov et al, 2001;Auradou et al, 2006;Huang et al, 2017aHuang et al, , 2017b. The hydraulic properties of natural fractures depend on the factors such as surface roughness, aperture distribution and the contact areas between the two opposing faces of the fracture (Baghbanan and Jing, 2008;Rasouli and Hosseinian, 2011;Jafari and Babadagli, 2013).…”
Section: Introductionmentioning
confidence: 99%